Mediation of Time‐Related Blood Pressure Variability on Intensive Blood Pressure Lowering and Functional Outcomes Post Endovascular Therapy: A Post Hoc Analysis of the OPTIMAL‐BP Trial - Jun Young Chang; Jae Young Park; Jeong Yun Song; Jun Sang Yoo; Kyu Bong Lee; Jae Wook Jung; Ji Sung Lee; Young Dae Kim; Byung Moon Kim; Bang‐Hoon Cho; Seong Hwan Ahn; Sung‐Il Sohn; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background We investigated whether the association between blood pressure (BP) management in patients with successful reperfusion following endovascular therapy (EVT) and functional outcomes is mediated by BP variability parameters. Methods and Results This is a post hoc analysis of the OPTIMAL‐BP (Outcome in Patients Treated With Intra‐Arterial Thrombectomy‐Optimal Blood Pressure Control) trial, conducted at 19 centers in South Korea. The primary outcome was the 90‐day functional outcome, assessed using the modified Rankin Scale. Multivariable logistic regression analysis was conducted for the association between BP variability and outcomes including 90‐day modified Rankin Scale score, symptomatic intracranial hemorrhage, and final infarction volume. Mediation analysis was performed to evaluate the causal inference whether the relationship between intensive BP management and the 90‐day modified Rankin Scale scoreis mediated by 24‐hour BP variability parameters (time rate [TR], SD, coefficient of variation, and variability independent of the mean). Among various BP variability parameters, higher TR was associated with an unfavorable ordinal shift of the 90‐day modified Rankin Scale score (adjusted odds ratio [aOR], 1.17 [95% CI, 1.04–1.32], P=0.007) and an increase in final infarction volume (β$$ β $$ coefficient, 21.24 [95% CI, 3.99–38.48], P=0.016), but did not increase the risk of symptomatic intracranial hemorrhage. TR fully mediated the association between intensive BP management and functional outcomes. The proportion of the association explained by TR was 40.93%. Conclusions TR mediated the relationship between intensive BP management and poor functional outcome in successfully reperfused patients with ischemic stroke by contributing to an increase in infarct volume. Efforts to modulate TR after EVT may be helpful in improving clinical outcomes.